Evaluación técnico-financiera de la inyección alternada de nitrógeno con generación in situ como mecanismo de recuperación mejorada de petróleo en un pozo de los campos Jazmín Y Girasol (2019)
During the last decades nitrogen injection it has been an efficient and cost-effective alternative, particularly in heavy oil recovery. Use as method EOR (Enhanced Oil Recovery) is offered as an alternative to increase production through optimal economic and operational techniques. In this research project a conceptual simulation model was developed to evaluate technical and financial alternating nitrogen injection in situ generation in a well of jasmine and sunflower fields as immiscible displacement mechanism oil considering the operational parameters required by the company in order to determine the best production stage and improve the economic viability of the projects.